Підтримання якості електроенергії для споживачів за допомогою нечіткої логіки - Демченко, Катерина Вікторівна; Піскарьов, Олексій Миколайович; Панов, Антон Олександрович; Галько, Сергій Віталійович; Середа, Анатолій Іванович; Demchenko, Kateryna; Piskarev, Oleksiy; Panov, Anton; Halko, Serhii; Sereda, Anatoliy (Запоріжжя : ТДАТУ, Видавничий дім «Гельветика», 2025)
UA: Відповідно до Енергетичної стратегії України на період до 2030 р., серед напрямів підвищення ефективності енергетичного сектору країни визначено контроль якості електроенергії для споживачів та регулювання напруги і показників якості електроенергії для досягнення стандартів якості. Для завдання нормалізації якості напруги в мережі запропоновано модель регулювання сталого відхилення напруги за допомогою нечіткої логіки, і на основі моделювання показано ефективність запропонованих алгоритмів. Алгоритм управління засновано на нечіткій логіці та розглядається як альтернатива переходу від аналогового управління до цифрової системи управління перемикачем відгалужень обмотки. Результати роботи можуть бути використані під час проєктування підстанції для впровадження в енергосистему. EN: In accordance with the Energy Strategy of Ukraine in the period up to 2030, among the directions for increasing the efficiency of the country's energy sector, the control of the quality of electricity for consumers and the regulation of voltage and indicators of the quality of electricity to achieve quality standards have been announced. It is known that in the sockets of the population of Ukraine there can be any voltage, and not the promised 220 Volt. Control of this power quality indicator should be performed by the supplier. Why does it turn out that the electric current becomes of poor quality and leads to emergency consequences. The reasons are many and can be various, and in this most often, but not to blame, the companies that supply electricity are to blame. Drops in network voltage, which can cause any consumer equipment to burn out. Power outages are an unpredictable phenomenon, they have existed and will always exist, as they depend on natural factors. However, voltage drops in the network can be regulated in the future, and consumers will be able to receive high-quality electricity. As a result of the load change, the voltage loss in the network also changes, and as a result, the voltage at the consumers' terminals changes. These changes can be fast and short-term (for example, during the start of an asynchronous motor with a short-circuited rotor) or slow and long-lasting (with a gradual change in load over the course of a day or year and with smooth voltage regulation). Therefore, a model of regulation of steady-state voltage deviation using fuzzy logic was proposed for the problem of normalizing voltage quality in the network. And on the basis of simulation, the effectiveness of the proposed algorithms is shown. A control algorithm based on fuzzy logic is considered as an alternative to the transition from analog control to a digital on-load tap-changer control system. Modeling of this system was carried out in the Fuzzy Logic Toolbox, included in the MATLAB package. Four fuzzy variables corresponding to phase voltages are considered as input parameters of the fuzzy output system: «Phase A», «Phase B», «Phase C» and «On-load tap-changer position», and four fuzzy variables are considered as output parameters: «Device switching», «On-load tap-changer», «Disconnecting part of the load», «Switching on an additional load» and «Switching on the additional voltage device». The results of this work can be used by electricity supply companies or individual users who plan to normalize the voltage quality in their electrical network.
Maintaining the quality of electricity for consumers with the help of fuzzy logic
Keywords: розподільна мережа; алгоритм управління; набори термінів; якість електроенергії; додаткове навантаження; distribution network; control algorithm; time sets; power quality; additional load